How group processes influence, maintain, and overcome health disparities. (July 2016) - Stone, Jeff; Kwan, Virginia S. Y.
This special issue of Group Processes and Intergroup Relations presents new theory and research on how group processes influence, maintain, and overcome health disparities. We present eight papers that document the causes and consequences of health disparities from the perspective of stigmatized and disadvantaged groups, health care providers, and during the course of interaction between patients and providers. Several papers describe interventions and other factors that have the potential to reduce differences in health and well-being. We hope the research in this collection inspires more investigators to consider how their work on group processes and intergroup relations can address, and help to eliminate, disparities in health outcomes for the disadvantaged.